Managerial drivers of Chinese labour loyalty in international construction projects - Zhu, Weina; Zeng, Ruochen; Li, Xiaodong; Zhu, Yi; Zhang, Zhihui (Journal of Civil Engineering and Management, 2017)
Organization performance is becoming ever more dependent on employee loyalty in the international construction projects. However, the improvement of construction labour loyalty on construction sites remains a largely neglected measure for reducing their turnover and improving their productivity. The purpose of this study was to quantitatively investigate the managerial drivers of labour loyalty, including macro-environment of the project host country, organizational living environment, job system, rewards, and communication, and to explore the significance of satisfaction as a mediating variable in the relationship between the managerial drivers and construction labour loyalty. First, hypotheses on the relationships between construction labour loyalty, satisfaction and the five managerial drivers were proposed. Second, structural equation modelling was adopted to test these hypotheses. Finally, the results demonstrated two types of influence paths: (1) macro-environment, job system and communication have significantly direct effects on construction labour loyalty, (2) mediated by satisfaction, organizational living environment and rewards offer positive indirect effects on construction labour loyalty. The first type of path serves as a long-term strategic orientation for improving labour loyalty. The second type of path is a tactic for short-term goals of labour loyalty enhancement. The research results can contribute to the body of knowledge of human resource management and the practice of enhancing labour productivity through improving construction labour loyalty in the context of international construction projects.